Horizontal Resistance Characteristics of Batter-Coupled Spiral Piles under Monotonic and Cyclic Loading - Kurokawa, Takahiro; Yasufuku, Noriyuki; Ide, Yuta; Nagata, Makoto (Lowland Technology International, 2024)
Spiral piles have high axial resistance and are used as foundations for small structures. On the other hand, spiral pileshave a lower bending rigidity than steel pipe piles of the same diameter, resulting in a problem of lower horizontal resistance.The authors have focused on a two-pile coupled pile structure with spiral piles, which is also resistant to horizontal forces, andhave conducted research to understand its resistance characteristics. In this study, model tests were mainlyconducted on coupled piles with two spiral piles as batter piles to understand their horizontal resistance characteristics.Monotonic loading tests on a dense dry sand showed that the use of spiral piles as batter piles provided higher elastic limitspring rigidity and horizontal yield load than single piles or vertically-coupled piles. Furthermore, the highest elastic limitspring rigidity was obtained when the angle of inclination of the batter pile was 45°. The durability of the batter piles under thesand conditions of this study was demonstrated by cyclic loading tests at a load equivalent to the horizontal yield load.